Examination of Fair Play Approaches of High School Students who Participate in School Sports and not - Tan, Çetin; Ceylan, Yusuf (Tamer KUTLUCA, 2023)
In order to improve people's behavior in line with the spirit of fair play, both in the world of athletics and in the social sphere, it is vital to challenge the phenomenon of fair play at all educational levels. All social actors agree that it is possible to establish communities in which fair play behaviors are common, but only with the education that must be provided from a young age. This study aims to investigate high school students’ perceptions of fair play, both among those who participate in and among those who do not participate in school sports. A total of 145 female students make up the study’s sample, including 104 female students studying in the Mardin province who have previously participated in volleyball at their schools and 41 female students who have not. Aside from the demographic information form created by the researchers, the “Multidimensional Sportsmanship Orientation Scale” was used as a data collection tool in the study. The package program SPSS 21.0 was used to analyze the information that had been gathered. The information collected from the participants was interpreted using frequency, percentage distributions, and nonparametric tests. Significant differences were found in the variables of age (in favor of older age), school type (in favor of imam hatip high school), and mother's employment status (in favor of non-working). Variables such as involvement in school sports, family income, mother’s education level, and father’s occupation were not found to differ significantly.

In order to improve people's behavior in line with the spirit of fair play, both in the world of athletics and in the social sphere, it is vital to challenge the phenomenon of fair play at all educational levels. All social actors agree that it is possible to establish communities in which fair play behaviors are common, but only with the education that must be provided from a young age. This study aims to investigate high school students’ perceptions of fair play, both among those who participate in and among those who do not participate in school sports. A total of 145 female students make up the study’s sample, including 104 female students studying in the Mardin province who have previously participated in volleyball at their schools and 41 female students who have not. Aside from the demographic information form created by the researchers, the “Multidimensional Sportsmanship Orientation Scale” was used as a data collection tool in the study. The package program SPSS 21.0 was used to analyze the information that had been gathered. The information collected from the participants was interpreted using frequency, percentage distributions, and nonparametric tests. Significant differences were found in the variables of age (in favor of older age), school type (in favor of imam hatip high school), and mother's employment status (in favor of non-working). Variables such as involvement in school sports, family income, mother’s education level, and father’s occupation were not found to differ significantly.
Examination of Fair Play Approaches of High School Students who Participate in School Sports and not
Keywords: Other Fields of Education (Other); Alan Eğitimleri (Diğer)